The 19 Fr. Intrauterine Bigatti Shaver (IBS®): a clinical and technical update - Bigatti, G (Facts Views Vis Obgyn, 2018)
In this case report we describe the first two surgeries conducted with the 19 Fr. IBS®. The indication for operative hysteroscopy in both patients was the removal of polyps. The size of the polyps was between 15 mm and 20 mm with a mean resection time of 40 seconds. Normal saline solution (500 ml) was used with a negative fluid loss (100 ml). Both operations were successfully performed under general anaesthesia and no speculum, no tenaculum and no dilatation of the cervical canal were necessary.